KLASIFIKASI PERANGKAT KERJA DI PT. INDONESIA COMNET PLUS DENGAN METODE DECISION TREE - Waluyo, Noviyan Jati; Noor Santi, Rina Candra (Jurnal informasi dan komputer, 2023)
Indonesia Comnets Plus (ICON+) is a Subsidiary of PT. PLN (Persero) Work equipment used by employees at ICON+ is supplied from 3 different vendors. Before the work equipment is connected to the ICON+ network, standardization must be carried out by the IT team. To determine the feasibility of the equipment to be standardized by the IT team, manual checks are carried out by the IT team on duty. For those that are appropriate, standardization can be done before connecting to the network. Meanwhile, if there are work equipment that does not meet the software requirements, the user can directly contact the vendor of the work equipment provider. To speed up the standardization process, a work device classification system is needed, using the Decision Tree C4.5 algorithm. Where device users can check independently. The results of the classification system will show the feasibility of the device to be standardized before connecting to the office network.